2023
DOI: 10.3390/ijms24054901
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic Arthritis: Pathogenesis and Targeted Therapies

Abstract: Psoriatic arthritis (PsA), a heterogeneous chronic inflammatory immune-mediated disease characterized by musculoskeletal inflammation (arthritis, enthesitis, spondylitis, and dactylitis), generally occurs in patients with psoriasis. PsA is also associated with uveitis and inflammatory bowel disease (Crohn’s disease and ulcerative colitis). To capture these manifestations as well as the associated comorbidities, and to recognize their underlining common pathogenesis, the name of psoriatic disease was coined. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 173 publications
0
20
0
Order By: Relevance
“…Moreover, the HLA-B*08.01 allele has been linked to asymmetric sacroiliitis, peripheral arthritis, ankylosis and increased join damage, and HLA-B*27 with symmetric sacroiliitis, dactylitis, and enthesitis [60]. On the other hand, polymorphisms in IL23R, TNFAIP3, PTPN22 (tyrosine-protein phosphatase non-receptor type 22), IL12B, RUNX1 (CD8-lymphocyte activation and differentiation), IL13, KIR (killer-cell immunoglobulin-like receptor), and MAGI1 genes have shown association with psoriatic arthritis [10,58]. Also, variants in the ADAMTS9 gene, involved in the cartilage extracellular matrix, are found to be associated with psoriatic arthritis [58].…”
Section: Genetics In Psoriatic Arthritismentioning
confidence: 99%
“…Moreover, the HLA-B*08.01 allele has been linked to asymmetric sacroiliitis, peripheral arthritis, ankylosis and increased join damage, and HLA-B*27 with symmetric sacroiliitis, dactylitis, and enthesitis [60]. On the other hand, polymorphisms in IL23R, TNFAIP3, PTPN22 (tyrosine-protein phosphatase non-receptor type 22), IL12B, RUNX1 (CD8-lymphocyte activation and differentiation), IL13, KIR (killer-cell immunoglobulin-like receptor), and MAGI1 genes have shown association with psoriatic arthritis [10,58]. Also, variants in the ADAMTS9 gene, involved in the cartilage extracellular matrix, are found to be associated with psoriatic arthritis [58].…”
Section: Genetics In Psoriatic Arthritismentioning
confidence: 99%
“…Ustekinumab effectively inhibits the differentiation of Th1 and Th17 cells. Phase 3 clinical trials (PSUMMIT trials 1 and 2) showed that this drug effectively treats skin manifestations, peripheral arthritis, enthesitis, and dactylitis in both TNFi-experienced and TNFi-naïve patients with PsA [15]. The use of ustekinumab resulted in a higher rate of achieving the primary outcome, defined as an ACR20 response at week 24, compared to the placebo group [97].…”
Section: Il-23 Inhibitors In Psamentioning
confidence: 99%
“…Neither of the IL-23 inhibitors has met the primary endpoint to be a considered as a treatment option for axSpA [15]. However, a post hoc analysis indicated potential efficacy of guselkumab in treating axial involvement in PsA [111].…”
Section: Il-23 Inhibitors In Psamentioning
confidence: 99%
See 1 more Smart Citation
“…The aetiology and pathophysiology of PsA are not fully understood, but they are thought to involve a complex interplay of genetic and environmental factors that trigger an abnormal immune and inflammatory response. 5 Several genes have been associated with PsA susceptibility and severity, such as HLA-B27, IL23R. 6 Environmental factors that may influence PsA development and progression include infections, trauma, stress, smoking, and alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%